Geology and geochemistry of oil and gas - Chilingar, George V., 1929- (Elsevier, 2005)
This book discusses the progress that is being made through innovations in instrumental measurements of geologic and geochemical systems and their study using modern mathematical modeling. It covers the systems approach to understanding sedimentary rocks and their role in evolution and containment of subsurface fluids. Fundamental aspects of petroleum geology and geochemistry, generation, migration, accumulation, evaluation and production of hydrocarbons are discussed with worldwide examples. Various physical and chemical properties of subsurface waters, crude oils and natural gases are described which is especially important to production engineering.-Among various properties of liquid and gaseous hydrocarbons the most important are wettability affecting production characteristics and ultimate recovery: relative permeability affecting reservoir fluid flow to the production wells; density differences between immiscible fluids which affects gravity drainage; viscosity of subsurface fluids affecting the relative mobility of each fluid; and fluid chemistry, which affects the absorption, ultimate recovery and monetary value of produced hydrocarbons.-Discussion of the formation and accumulation of hydrocarbons includes (1) the changes in the chemical composition of hydrocarbons that originate from the debris of living plants and organisms to form crude oil and natural gas; (2) the origin of hydrocarbons in different areas of a single reservoir; (3) the conditions, which determine the distribution of water, oil and gas in the reservoir; (4) the migration of subsurface fluids until they eventually accumulate in isolated traps; (5) discussion of the traps as a function of sedimentary geology and tectonics. This is based on the systems approach to the specific geologic and geochemical systems using analytical and statistical principles and examples of modern mathematical modeling of static and dynamic systems.-* Discusses fundamental aspects of petroleum geology and geochemistry, and generation, migration, accumulation, evaluation and production of hydrocarbons * Presents a systems approach to the specific geologic and geochemical systems.
Keywords: Petroleum -- Geology.; Natural gas -- Geology.; Geochemistry.; elektronické knihy; electronic books